Pain Management in Burn Patients - Rodrigo José Alencar de Castro; Plínio Cunha Leal; Rioko Kimiko Sakata (Brazilian Journal of Anesthesiology, 2013)
Background and objectives: : Despite advances, inappropriate analgesic treatment for burn patients is still seen. The objective of this review was to collect data on pain management in burn patients. Content: : We reviewed the mechanisms of pain, burn patient assessment, as well as pharmacological and non-pharmacological treatment. Conclusion: : Pain management in burn patients is still a challenge for the multidisciplinary team. Frequent and continuous evaluation of the patient's response is very important due to the various stages that the hospitalized burn patient goes through, as well as a combination therapy with analgesic and non-pharmacological measures. Understanding the complexity of the pathophysiological, psychological, and biochemical changes a burn patient presents is the ﬁrst step to achieve success in analgesic management. Keywords: Acute Pain, Analgesia, Burns, Chronic Pain